The Devil Is in the Details : Growth, Polarization, and Poverty Reduction in Africa in the Past Two Decades - Clementi, F.; Fabiani, M.; Molini, V. (World Bank, Washington, DC, 2018)
This paper investigates the distributional changes that limited pro-poor growth in the past two decades in Sub-Saharan Africa; these changes went undetected by standard inequality measures. By developing a new decomposition technique based on a nonparametric method -- the relative distribution -- the paper finds a clear distributional pattern affecting almost all the analyzed countries. Nineteen of 24 countries experienced a significant increase in polarization, particularly in the lower tail of the distribution, and this distributional change lowered the pro-poor impact of growth substantially. Without this change, poverty could have decreased an additional 5-6 percentage points during the past decade.